2007
DOI: 10.1016/j.diabres.2006.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea and glinide reduce insulin content, functional expression of KATP channels, and accelerate apoptotic β-cell death in the chronic phase

Abstract: We previously found that chronic exposure to glibenclamide inhibits acute glibenclamide-induced insulin secretion by reducing the number of functional ATP-sensitive K(+) (K(ATP)) channels on the plasma membrane of pancreatic beta-cells. In the present study, we compared sulfonylurea-induced and glinide-induced insulin secretion in pancreatic beta-cells chronically exposed to these widely used oral hypoglycemic agents. Chronic exposure of pancreatic beta-cells to sulfonylureas (glibenclamide or tolbutamide) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Although we had these study limitations, these results, together with previous reports, suggest that remission may associate with disuse of sulfonylurea prior to insulin therapy in outpatients with T2DM. The findings are also compatible with reports indicating that long-term overstimulation of β-cells by sulfonylureas may exhaust β-cell function [7,8].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although we had these study limitations, these results, together with previous reports, suggest that remission may associate with disuse of sulfonylurea prior to insulin therapy in outpatients with T2DM. The findings are also compatible with reports indicating that long-term overstimulation of β-cells by sulfonylureas may exhaust β-cell function [7,8].…”
Section: Discussionsupporting
confidence: 81%
“…Sulfonylureas may reduce insulin secretion, resulting in desensitization from long-term overstimulation [7,8]. One study reported that most T2DM patients who stopped insulin after intensive insulin therapy had not been treated with sulfonylureas, whereas most of those who continued with insulin had [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed over the past few years have suggested that some imidazoline derivatives may stimulate insulin secretion in a more glucose-dependent fashion than sulphonylureas [10,11]. Thus, the inherent risk of hypoglycaemias caused by the therapeutic use of sulphonylureas may be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while the effects of GLP1 on pancreatic hormone secretion are glucose dependent, which virtually eliminates the risk of hypoglycaemia, the actions of insulin and SUs are not dependent on elevated glucose levels, and thus therapies with these agents lead to much higher rates of hypoglycaemia. Furthermore, while non-glucose-dependent insulin secretagogues, such as SUs, may place excessive stress on pancreatic b-cells and potentially promote b-cell apoptosis (Maedler et al 2005, Takahashi et al 2007, Aston-Mourney et al 2008, incretins activate signalling pathways that provide protection against apoptosis (Trumper et al 2002, Hui et al 2003, Wang et al 2004. Preclinical studies in rodents have provided hope that enhancing GLP1R signalling may be able to halt the progressive decline in b-cell mass and perhaps even promote the growth of new b-cells in vivo (Xu et al 1999, Stoffers et al 2003).…”
Section: Introductionmentioning
confidence: 99%